THE IMPORTANCE OF PROJECT-BASED TECHNOLOGY IN APPLYING MODERN TECHNOLOGIES IN MUSIC LESSONS (Scientific journal of the Fergana State University, 2025)
This article discusses the project technology of using modern technologies in music lessons, ways of introducing advanced teaching methods using modern pedagogical and information and communication technologies and at the same time sheds light on the use of the music education system. . attention is paid to.